2016
DOI: 10.1007/s11192-016-1922-5
|View full text |Cite
|
Sign up to set email alerts
|

A delineating procedure to retrieve relevant publication data in research areas: the case of nanocellulose

Abstract: Advances concerning publication-level classification system have been demonstrated striking results by dealing properly with emergent, complex and interdisciplinary research areas, such as nanotechnology and nanocellulose. However, less attention has been paid to propose a delineating method to retrieve relevant research areas on specific subjects. This study aims at proposing a procedure to delineate research areas addressed in case nanocellulose. We investigate how a bibliometric analysis could provide inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…A single research area can contain hundreds or thousands of publications clustered. The use of this publication-level classification system proved to be effective to enhance the precision on information retrieving task in earlier study 32 . Figure 2 depicts the procedure for retrieving information, and to develop, visualize and analyze the indicators.…”
Section: Bibliometric Analysis and Science Mapsmentioning
confidence: 81%
See 2 more Smart Citations
“…A single research area can contain hundreds or thousands of publications clustered. The use of this publication-level classification system proved to be effective to enhance the precision on information retrieving task in earlier study 32 . Figure 2 depicts the procedure for retrieving information, and to develop, visualize and analyze the indicators.…”
Section: Bibliometric Analysis and Science Mapsmentioning
confidence: 81%
“…In this paper we use a specific Publication-level Classification System 31 , which can be represented in maps, to retrieve relevant publications about our topic of interest. Previous research showed us that delineating a sample of publications using this system is more effective than regular Boolean searches in databases because it enhances the precision of the search 32 . Two bibliometric concepts that deserve more attention in the context of this study are co-authorship and citation analysis.…”
Section: Amorphous Metallic Alloys Applied By Thermal Spraying Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hullmann & Meyer, 2003;Porter, Youtie, Shapira, & Schoeneck, 2008;Schummer, 2004). This class contains 285 articles, including three articles mentioning nanocelluloses in their titles (Milanez, do Amaral, Lopes de Faria, & Rodrigues Gregolin, 2013, 2014Milanez et al, 2016). A third reason to study nanocelluloses is that we are somewhat familiar with this subject area, since we have studied it in our practice on demand of a client.…”
Section: The Case Of Nanocellulosesmentioning
confidence: 99%
“…The first counting resulted in 36 relevant publications and 64 irrelevant ones. Following (Milanez et al 2016) we decided to exclude some publications with an iterative cleaning procedure that excluded papers containing certain keywords that are not relevant in for our field, by adding them in the query with the BAND NOT^operator. After each iteration when new words were added to the query, we checked random samples of 100 papers that were part of the biggest connected graph to ensure that they were rightly kept and a similar sample of the papers that were now excluded (ending up in the 'ring of Saturn') to check whether this was fair.…”
Section: Delineating the Corpusmentioning
confidence: 99%